Systemy informatyczne wspomagające funkcjonowanie urzędów skarbowych - Gadomski, Sebastian (Information systems supporting the functioning of the revenue offices, 2005)
In the article the author presents information systems supporting the work of revenue offices. Based on the accepted criteria, a general classification was made into three groups. Subsequently respective systems were discussed and their utility extent taken into consideration. In the summary it is pointed out that developing the autonomic programs is not advisable but that developing central systems for assurance of integrity and cohesion of the data in macro as well as micro scale is significant. It guarantees the uniformity and cohesion of the transferred data from the revenue offices and revenue chambers to the Ministry of Finance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 27-39